Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan Pada PT Maztrans Global Indo - Dhaifan Arrash, Muhammad; Ivantan Ivantan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The purpose of this research is to determine the effect of service quality and promotion on customer satisfaction at PT Maztrans Global Indo. This research method uses quantitative research methods. The population in this study were customers at PT Maztrans Global Indo with a sample of 81 respondents. The data collection technique uses a questionnaire technique. The data analysis used was data instrument test, classical assumption test, linear regression test, correlation test, and determination test using the SPSS version 26 program. The results of partial hypothesis testing between service quality and customer satisfaction obtained a t value of 3.008 > 1.99125 with a significance level of 0.004 < 0.05, so H0 was rejected and Ha was accepted. The results of partial hypothesis testing between promotion and customer satisfaction obtained a t value of 3.088 > 1.99125 with a significance level of 0.187 < 0.05, so H0 was rejected and Ha was accepted. The results of simultaneous hypothesis testing with a value of Fcount 42,563 > Ftable 3.12 with a significance level of 0.000 < 0.05, thus Ho is rejected and Ha is accepted. The results of the coefficient of determination of service quality and promotion simultaneously contribute to the customer satisfaction variable of 52,2%, while the remaining 47,8% is caused by other variables Keywords: Service Quality, Promotion and Customer Satisfaction